Acetylsalicylic acid, aging and coronary artery disease are associated with ABCA1 DNA methylation in men - Guay, Simon-Pierre (BioMed Central, 2014)
BACKGROUND: Previous studies have suggested that DNA methylation contributes to coronary artery disease (CAD) risk variability. DNA hypermethylation at the ATP-binding cassette transporter A1 (ABCA1) gene, an important modulator of high-density lipoprotein cholesterol and reverse cholesterol transport, has been previously associated with plasma lipid levels, aging and CAD, but the association with CAD has yet to be replicated. RESULTS: ABCA1 DNA methylation levels were measured in leucocytes of 88 men using bis-pyrosequencing. We first showed that DNA methylation at the ABCA1 gene promoter locus is associated with aging and CAD occurrence in men (P < 0.05). The latter association is stronger among older men with CAD (≥61 years old; n = 19), who showed at least 4.7% higher ABCA1 DNA methylation levels as compared to younger men with CAD (<61 years old; n = 19) or men without CAD (n = 50; P < 0.001). Higher ABCA1 DNA methylation levels in older men were also associated with higher total cholesterol (r = 0.34, P = 0.03), low-density lipoprotein cholesterol (r = 0.32, P = 0.04) and triglyceride levels (r = 0.26, P = 0.09). Furthermore, we showed that acetylsalicylic acid therapy is associated with 3.6% lower ABCA1 DNA methylation levels (P = 0.006), independent of aging and CAD status of patients. CONCLUSIONS: This study provides new evidence that the ABCA1 epigenetic profile is associated with CAD and aging, and highlights that epigenetic modifications might be a significant molecular mechanism involved in the pathophysiological processes associated with CAD. Acetylsalicylic acid treatment for CAD prevention might involve epigenetic mechanisms.